ANALISIS PENGARUH KARAKTERISTIK PERSONAL TERHADAP PERILAKU MENYIMPANG PELAKSANAAN AUDIT - Ridaryanto, Petrus (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This study aims to analysis the impact of personal characteristic toward dysfunctional audit behaviour. The characteristic personal as independent variabel consist of gender, education level and job experience.Sample in this research is auditors who work in Public Accounting Office in Jakarta. Data is collected by quetioner and the result survey is 130 auditors.Data analysis used Statistical Package for the Social Sciences versi 24.The result of this study show that education and job experience have effected toward dysfunctional audit behavior, while gender has not effected toward dysfunctional audit behavior.